Comparative analysis of relative gene expression data reveals novel microRNAs in the artery of rats with renovascular hypertension - Yu, Hui; Hu, Hai; Wang, Zhanli (Archives of Biological Sciences, 2020)
Paper description: The regulatory mechanisms of vascular dysfunction in rats with renovascular hypertension are poorly understood. MiRNA sequencing was performed to investigate the gene regulatory pathways associated with vascular dysfunction in rats with renovascular hypertension. We identified 17 miRNAs that were differentially expressed. These miRNAs were associated with immune-inflammatory and metabolic pathways involved in vascular dysfunction. Treatment with losartan maintained their expression and the levels of cytokines. Our results provide valuable information on mechanisms of miRNA-mediated vascular function regulation in 2K1C rats with renovascular hypertension. Abstract: Hypertension is associated with impaired vascular endothelial function. However, the regulatory mechanisms of vascular dysfunction in rats with renovascular hypertension (RVH) remain poorly understood. In this study, the 2-kidney-1-clip (2K1C) hypertensive rat model was utilized. Next-generation sequencing was then used to detect microRNA (miRNA) expression profiling in the arteries of 2K1C rats. We identified 17 miRNAs that were differentially expressed in the 2K1C group compared with the sham group, of which 9 were downregulated and 8 were upregulated. These differentially expressed miRNAs were found to be associated with immune/inflammatory and metabolic pathways, which are involved in vascular dysfunction. Treatment with losartan maintained the expression of the differentially expressed miRNAs, miR-31a-5p and miR-142-3p, and the levels of TNF-α, IL-1β, IL-6 and MCP-1, indicating that the differentially expressed miRNAs and their associated immune/inflammatory pathways play a pivotal role in the modulation of the vascular dysfunction in 2K1C rats. Our study provides valuable information about miRNA expression in the arteries of 2K1C rats, expanding our understanding of the complex molecular mechanisms underlying the vascular dysfunction in rats with RVH.